Sensing Different Micellar Microenvironments with Solvatochromic Dyes of Variable Lipophilicity - Caroli-Rezende, M; Aliaga-Vidal, C; Aliaga-Vidal, C; Mascayano-Collado, C; Briones, J (2011)
The UV/Vis spectral behavior of three solvatochromic N-alkyl ?-pyridones of varying lipophilicity was investigated in aqueous solutions of a block copolymer at variable temperatures. The solvatochromic responses of the three analogues to the distinct microenvironments were compared and interpreted in terms of their different location in the microheterogeneous system. The interpretation was supported by 1H NMR measurements and by molecular dynamics simulations that mimicked the interactions of the dyes with the polymeric micelle in water. © 2011 Elsevier Ltd. All rights reserved.